(untitled) (IITM Journal of Business Studies, 2025)
he effectiveness of digital marketing strategies in boosting online business sales through social media platforms is a critical area of study in today’s digital age. This research aims to delve deeply into how businesses can leverage social media for marketing purposes to enhance their sales performance. Digital marketing has become indispensable for businesses aiming to reach and engage with their target audiences effectively. Social media platforms, such as Facebook, Instagram, Twitter, LinkedIn, and others, have emerged as powerful tools for marketers because of their extensive user bases and advanced targeting capabilities. These platforms enable businesses to create targeted advertising campaigns, share engaging content, interact directly with customers, and leverage influencer partnerships to increase brand visibility and drive sales. This research serves as a comprehensive guide for businesses seeking to harness the power of social media to increase their online sales through effective digital marketing strategies. By synthesizing theoretical knowledge with empirical findings, this study provides actionable insights and best practices that businesses can implement to optimize their digital marketing efforts, maximize revenue generation, and cultivate long-term customer relationships in the digital era.